DESIGN OF DASHBOARD FOR WEBSITE BASED TEACHER PERFORMANCE MONITORING (CASE STUDY: SMAN 2 SUMBAWA BESAR) - Danu Kristantio; Henry Bambang Setyawan; I Gusti Ngurah Alit Widana Putra (Jurnal Sistem Informasi Universitas Dinamika, 2021)
State Senior High School (SMAN) 2 Sumbawa Besar is one of the educational institutions in Sumbawa Besar which has been established since July 1977 and has been accredited A. SMAN 2 is also one of the favorite schools. SMAN 2 Sumbawa Besar is located at Jl. Garuda 102 Sumbawa Besar. In the current monitoring implementation process, school supervisors have to come to the school and check the teacher performance assessment team on teacher performance so that it takes a long time to obtain total information. From the current monitoring process, the problem is that supervisors and principals need a long time to find out information on the performance of all teachers. The proposed solution given to solve the problem is the Dashboard application to monitor the performance of web-based teachers at SMAN 2 Sumbawa Besar. This dashboard will provide a display of graphic information including: 1) the number of teachers who are Civil Servants (PNS) and Honorary. 2) Number of teachers by gender. 3) The number of teachers with the latest education. 4) The average score of all teachers per period to see the development of teacher performance from the initial period to the last period. 5) The average performance score of all teachers based on the competencies per period (the teacher performance competencies in question are Pedagodic, Personality, Social, Professional). 6) The acquisition of each teacher's score based on the competence of each teacher 7) The acquisition of teacher scores based on the indicators of teacher performance competence. 8) Average teacher attendance per period. Based on the results of trials conducted with the school, this application can display teacher performance results in graphical form, easy to use and easy to access without having to install other applications, and shorten the time for principals and supervisors to monitor teacher performance.